Is Human Capital the Key to the IT Productivity Paradox? - Erik Mellander; Eleni Savvidiou; Gudmundur Gunnarsson (The Research Institute of Industrial Economics (IUI), 2001)
Unlike previous analyses, we consider (i) that IT may affect productivity growth both directly and indirectly, through human capital interactions, and (ii) possible externalities in the use of IT. Examining, hypothetically, the statistical consequences of erroneously disregarding (i) and (ii) we shed light on the small or negative growth effects found in early U.S. studies, as well as the positive impacts reported recently. Our empirical analysis uses a 14-industry panel for Swedish manufacturing 1986-95. We find that human capital developments made the average effect of IT essentially zero in 1986 and steadily increasing thereafter, and, also, generated large differences in growth effects across industries.
Keywords: D24; J24; L60; 330; IT-human Capital Complementarity; New Growth Theory; Applied Econometrics; Informationstechnik; Produktivität; Humankapital; Neue Wachstumstheorie; Schätzung; Schweden